Halal industries growth in Salatiga, Central Java, Indonesia - Annisa, Arna Asna (Asian Management and Business Review, 2023)
This study aims to see the growth performance of the halal industry through the perspective of business actors within the framework of tolerance and the creative economy. The city of Salatiga was chosen as the research location because it has the achievement of being the most tolerant city in Indonesia; this is a new reference base for developing the halal industry from a sociocultural perspective. Through qualitative research with a case study approach, the key person for this research is the Head of the MSMEs Division of the Cooperatives and MSMEs Office of Salatiga City and 22 MSMEs entrepreneurs who will receive free halal certification services in 2021. The data obtained in the form of primary data are analysed using the Atlas t.i application. The data is then validated through triangulation of data with secondary data. The research instrument was developed from the halal balanced scorecard theory, which has four (4) perspectives: learning and growth, internal business, customer, and financial. The results of the data analysis show that government support significantly impacts the process of growing MSMEs awareness to learn to provide halal guarantees for the products they produce. This affects their internal business, so they always evaluate critical points in their production activities. This is done because running a business on a consumer-oriented basis so that halal needs must be met to gain consumer confidence in the end financially, their income has increased. Based on these results, this research can be a recommendation for BI, KNEKS, and the Ministry of Cooperatives and MSMEs to determine the policy direction for developing MSME-based halal industries based on the approach of social and cultural values that still need to be prioritised.